Peran DISDUKCAPIL dalam Pengawasan Penyelenggaraan Administrasi Kependudukan bagi Orang Asing - Rachmawati, Aulia (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Along with the arrival of foreign colors from various countries to the city of Surabaya, causing smuggling. In population documents about Certificate of Residence (SKTT) of Foreigners is very necessary now to know that it is legal or illegal if you want to live in Surabaya. So the purpose of this research is to find out the supervision of the implementation of SKTT Foreigners who come and will settle in the city of Surabaya, so that there is no smuggling or illegal activities. Descriptive qualitative approach with the intention of providing a comprehensive picture with data collection techniques of observation, interviews, and documentation. Getting new findings, namely on the role of the Population and Civil Registration Office in Supervising the Implementation of SKTT Foreigners in Surabaya City from the three sub-focuses in terms of setting work standards, there are still obstacles in delivering information so that there was unclear information. However, the measurement of work results and corrective actions are optimal enough to provide services and preventive efforts so that nothing untoward happens in the future.